Sosialisasi Bahaya Pernikahan Dini Sebagai Upaya Pencegahan Stunting di Desa Selaawi Kecamatan Pasawahan - Salsabila Khairunnisa; Nunung Kurniasih; Akke Azhar Annisa; Gussevi, Sofia (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2025)
Nowadays, times have become modern with many changes in traditions and the social environment, as well as regulations that have been updated, but it cannot be denied that there are still many people who adhere to old traditions such as marrying off their children quickly where the children have not yet reached the age of readiness for marriage, both legally and health wise, so the number of early marriages in Indonesia continues to increase every year. Factors that cause early marriage in society are based, among other things, on inadequate economic conditions and low levels of education. The aim of community service through early marriage outreach is to provide education to teenagers in Selaawi village about the dangers of early marriage as an effort to prevent stunting. The method used is observation, planning and socialization by presenting the material followed by a question and answer session. As a result of this socialization activity, teenagers become aware of and understand the negative impacts of early marriage, such as health, psychological, educational, economic and social impacts and their relationship to the causes of stunting. They also become aware of the factors that influence early marriage, namely economic factors, family factors, educational factors, environmental factors, mass media factors, promiscuity factors, and thought/mindset factors.